Exploring Participatory Management in Social Enterprise Practice: Evidence from Chile - Radrigan-Rubio, M; Muñoz-Canales, C (Springer, 2021)
Although evidence shows that it is challenging to implement, many authors state that participatory management is a distinctive attribute of social enterprises. This paper presents case study research exploring how participatory management is manifest in Chile, a country where a paternalistic and autocratic management style prevails thereby constraining the adoption of more collaborative approaches. We found that a majority of the twenty social enterprises considered, despite having very different sizes, governance structure and activity sectors, involved employees and stakeholders in shared decision-making processes. Participatory management was exhibited in distinctive and diverse ways ranging from common agreement on strategic decisions through to the presentation of new proposals by members. We conclude that social enterprises in Chile differ from conventional enterprises not only in their focus on trying to solve social problems, but also in the fact that they may provide a vehicle to promote more innovative and participatory approaches to decision making. © 2021, International Society for Third-Sector Research.